Does the growth process discriminate against older workers? - François Langot; Eva Moreno-Galbis (Institute for the Study of Labor (IZA), 2008)
This paper seeks to gain insights on the relationship between growth and unemployment, when considering heterogeneous agents in terms of age. We introduce life cycle features in the endogenous job destruction framework à la Mortensen and Pissarides (1998). We show that, under the assumption of homogeneous productivity among workers, firms tend to fire older workers more often than young ones, when deciding whether to update or not a technology: there is an equilibrium where the creative destruction effect dominates over the capitalization effect for old workers, whereas the capitalization effect dominates for young workers. This discrimination against older workers can be moderated when we introduce heterogeneity (in terms of productivity) among workers. We also provide empirical support for these theoretical findings using OECD panel data and numerical simulations of the model.
urn:nbn:de:101:1-2008120201
Keywords: J14; 330; TFP growth; unemployment by age; old workers' employment rate; capitalization; creative destruction effect; Arbeitslosigkeit; Altersgruppe; Arbeitsproduktivität; Wirtschaftswachstum; Technischer Fortschritt; Innovationsdiffusion; Theorie; OECD-Staaten